(untitled) (Biological Sciences - PJSIR, 2023)
In order to determine the fatty acids composition by Gas Chromatography (GC) of four native oyster species, samples of candidate oyster species (Ostrea nomades, Saccostrea cucullata, Crassostrea gryphoides and C. madrasensis) were obtained during June2008 from Buleji rocky Intertidal zone (24° 50’ N, 66° 48’ E) and deltaic zone of Hub river (24° 54’ N, 66° 43’ E) situated along the Sindh and Balochistan coast respectively. Present work unveils the variability in fatty acids components in four oyster species that have been investigated for the first time from Pakistan. A total of thirty nine (39) compounds, in aforementioned species were present comprised of saturated (SFA) mono-unsaturated (MUFA) poly- unsaturated fatty acids (PUFA)including dimethyl acetals (DMA) non-methylene interrupted acids (NMI) were isolated and among these poly-unsaturated fatty acids (PUFA) amounted larger proportion in all four species, about 50.02±0.15 mg/g in O. nomades, 49.07±1.63 in C. gryphoides, 47.93±4.82 mg/g in C. madrasensis and 45.51±3.34 mg/g in S. cucullata. Conspicuously 20:1n-9 and 22:1n-9 compounds were only present in S. cucullata, whereas these fatty acids were completely missing in other three species. Moreover, 20:3n-3 was found in trace amount in three species excluding C. madrasensis